1992
DOI: 10.1002/pro.5560010103
|View full text |Cite
|
Sign up to set email alerts
|

Differences in hydrogen exchange behavior between the oxidized and reduced forms of Escherichia coli thioredoxin

Abstract: Amide proton exchange of thioredoxin is used to monitor the structural effects of reduction of its single disulfide. An effective 3–5‐proton difference between the oxidized and reduced protein form is observed early in proton out‐exchange of the whole protein, which is independent of temperature in the range of 5–45 °C, indicating that redox‐sensitive changes are probably not due to low‐energy structural fluctuations. Medium resolution hydrogen exchange experiments have localized the redox‐sensitive amide prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Because the first &strand also has a large positive free energy of solvation and it is only 10 A from the active site, it is possible that cooperative changes occur at this site as well. These two regions correspond closely to the peptides that undergo a change in amide proton exchange rates upon reduction of thioredoxin (Kaminsky & Richards, 1992). The adiabatic compressibility of reduced thioredoxin is in the middle of the published range of -1 .O to t 1 2 .…”
Section: Sm Kaminsky and F M Richardsmentioning
confidence: 62%
See 1 more Smart Citation
“…Because the first &strand also has a large positive free energy of solvation and it is only 10 A from the active site, it is possible that cooperative changes occur at this site as well. These two regions correspond closely to the peptides that undergo a change in amide proton exchange rates upon reduction of thioredoxin (Kaminsky & Richards, 1992). The adiabatic compressibility of reduced thioredoxin is in the middle of the published range of -1 .O to t 1 2 .…”
Section: Sm Kaminsky and F M Richardsmentioning
confidence: 62%
“…In NMR experiments Hiraoki et al (1988) and Dyson et al (1990) found redox-sensitive changes, including hydrogen exchange properties, in the region of the SS bond. In the previous paper Kaminsky and Richards (1992) have corroborated that there is a small group of amide protons whose exchange behavior is dramatically altered by the redox state. These appear to occur in two small nonadjacent regions, the disulfide loop and the first 6strand.…”
mentioning
confidence: 78%
“…Recently, Dyson et al (1994) confirmed that the overall structure of the tnutant [Ser32, Ser35lTrx of E. coli thioredoxiii is very similar to that of the wild-type thioredoxin. Two regions are significantly more mobile than the average: the Nterminus and the active site (Kaminsky and Richards, 1992a;Stone et al, 1993). Substitution of glycine for serine at position 74 does alter the backbone structure.…”
Section: Discussionmentioning
confidence: 99%
“…New structural inforimtion oht;iined frorri models constructcd from tliioi-cdoxins of several oi-ganisnis, bascd on NMK sludies (Dyson ct al., 1989; Forinan-Kay e l al., 1989; Kaminsky and Richards, 19922;Stone et ul., 1993;Jeng el al., 1994) and o n the crysrallographic structure of E. coli thioredoxin, indicates that 311 protcins have similar throc-dimcnsiunal struclures dcspite the large variation in arnino acid sequences (Ekliind ct al., 1091). Two nun-adjacent regions, either in the linear sequence or in thrcc-dimensional space, exhibit changes upon reduction : the active site, residues 32-35, and a region within residues 1 -I3 at the N-terminal end (Kaminsky and Richards, 1992a;Stone Thioredoxin from Rho$ohrrcfcr sp/iwmi&s is similai-to E. coli thiorediixin and exhibits 47 % arnino acid identity to this protein. We have previously shown that the expression of R. S/JhLWI'Oim't'S thioredox in from ii recoinhiiiant plasmid, i ntroduccd into ii mutant of E. roli lacking thioredoxin, can restorc thc growth 01' phagc T7 (Pille ct al., 1990).…”
mentioning
confidence: 99%
“…Oxidation of the NTD slightly increases stability and causes increased internal fluctuations (wider well) of rapidly interconverting states on an intermediate timescale (rougher well). Oxidation of Ec Trx increases stability (49) and decreases the conformational heterogeneity (51, 52) (narrower well) without large changes in intermediate timescale motions (50) (similar roughness).…”
Section: Figures and Tablesmentioning
confidence: 93%